Experiences with the Telovelar Approach to Fourth Ventricular Tumors in Children - Zaheer, S. Noman; Wood, Martin (Pediatric neurosurgery, 2010)
Background: Fourth ventricular tumors are amongst the most common tumors in the pediatric population. Traditionally, these tumors are approached through the cerebellar vermis, but the telovelar approach is now becoming widespread. Posterior fossa syndrome/cerebellar mutism is a complication of surgery for fourth ventricular tumors whose precise cause remains elusive, but may be related to the surgical approach or injury to adjacent cerebellar structures. We present a small series of fourth ventricular tumors and our initial experience in using the telovelar approach for this surgery. Methods: Twenty patients with fourth ventricular tumors were operated on using the microsurgical telovelar approach, sparing the cerebellar vermis. Data were collected prospectively for all patients with respect to the degree of resection achieved, complications and the incidence of posterior fossa syndrome. Results: A complete resection was achieved on postoperative MRI in 70% of the patients. Residual disease <1.5 cm 3 remained in 15% and a further 15% had subtotal resection with >1.5 cm 3 of residual disease. Thirty percent had evidence of posterior fossa syndrome in the postoperative period, of which 84% had resolved at the last follow-up. Thirty percent of the patients developed symptomatic hydrocephalus requiring shunting. There were no new neurological deficits and no procedure-related deaths. Conclusion: The telovelar approach provides excellent access to tumors of the fourth ventricle with sparing of the vermis in children. The high incidence of cerebellar mutism in our patients confirms that this phenomenon is unlikely to be related to vermian injury and further study is recommended.